Bis(acetato-κO)(di-2-pyridylamine-κ(2) N (2),N (2′))palladium(II) - Ha, Kwang (International Union of Crystallography, 2012)
In the title complex, [Pd(CH(3)COO)(2)(C(10)H(9)N(3))], the Pd(II) ion is four-coordinated in a slightly distorted square-planar environment by two pyridine N atoms of the chelating di-2-pyridylamine (dpa) ligand and two O atoms from two anionic acetate ligands. The dpa ligand coordinates the Pd(II) atom in a boat conformation of the resulting chelate ring; the dihedral angle between the pyridine rings is 39.3 (2)°. The two acetate anions coordinate the Pd(II) atom as monodentate ligands and are located on the same sides of the PdN(2)O(2) unit plane. The carboxylate groups of the anionic ligands appear to be delocalized on the basis of the C—O bond lengths. Two complex molecules are assembled through intermolecular N—H⋯O hydrogen bonds, forming a dimer-type species. Intermolecular C—H⋯O hydrogen bonds further stabilize the crystal structure.